Significación del paso a la vida civil de una excombatiente de las FARC (2019)
In the post-conflict framework in Colombia, the processes of disarmament and reintegration of the ex-members of the FARC have begun, which represents a change not only for the country in general, but also for the people who were part of the armed group. The objective of this research is to investigate by means of qualitative methods (semi-structured interview and sentence completion). How an ex-combatant, who voluntarily linked to the armed group, means her passage to civil life?The cultural historical approach allowed to approach the study from a particular perspective with which the singularity of the participant was understood. In this case, it is considered pertinent, to propose differentiated interventions, by the educational level (higher education) of our participant.